Optimization of enzymatic protein extraction from beans - doi: 10.4025/actascitechnol.v32i3.6277 - Lopes Junior, Carlos de Oliveira (2010)
Considering the importance of beans in the Brazilian diet and the fact that it is forbidden in phenylketonuric feeding, it is relevant to promote the extraction of its proteins, for phenylalanine removal. Aiming for the optimization of protein extraction from beans, two enzymatic methods were initially employed. For the one that produced the highest protein extract yield (PEY), a study was conducted to assess de effect of several parameters, such as centrifugation velocity, reaction time, initial pH and type of enzyme (one of Bacillus licheniformis, two of Bacillus subtilis, one of Aspergillus sojae and one of Papaya carica). The results showed that the best method was the one that employed a concentration of raw material of 1:10 (w v-1), initial pH of 10.5, temperature of 50°C, in the absence of ultra-turrax treatment. With regard to the parameters tested, the largest PEY (93.1%) was obtained by using the enzyme from Bacillus licheniformis, the centrifugation velocity of 10,640 x g, the reaction time of 3h and initial pH of 10.5.